The zebrafish Genetics, genomics, and transcriptomics - Detrich, H. William III; Westerfield, Monte; Zon, Leonard I. (Methods in cell biology, 2016)
The Zebrafish: Genetics, Genomics, and Transcriptomics, Fourth Edition, is the latest volume in the Methods in Cell Biology series that looks at methods for the analysis of genetics, genomics, and transcriptomics of Zebrafish. Chapters cover such topics as gene-trap mutagenesis, genetic Screens for mutations, gene editing in zebrafish, homologous gene targeting, genome-wide RNA tomography, and developmental epigenetics and the zebrafish interactome.--Provided by publisher.